Development of hotel and restaurant business in Ukraine on the conditions of franchise and modern animation programs (Economics and region, 2022)
The article examines the trends in the hotel and restaurant business over the past three years. Recent years have been a real challenge for the tourism industry, which has developed rapidly over the past decade. For the first time in the 21st century, the COVID-19 pandemic has led to restrictions on the movement of citizens between cities, regions and states. Closure of all business entities and introduction of remote technologies. This has led to a large number of bankruptcies among hotels and restaurants. Quarantine restrictions did not allow for a high level of food visits, and remote technologies reduced the need for hotels. The authors found that the franchise market developed in Ukraine, in particular in the field of catering, even during quarantine. Franchising is recognized in the world as the most progressive form of business. The conditions it offers are favorable for entrepreneurs starting their business, as they significantly reduce the risk of failure and loss of funds. For example, in the United States, only 5 percent of franchised businesses fail in the first five years of existence, while 90 percent of other small businesses go bankrupt. The share of franchising in US retail sales is 34%, in Europe – 12% and continues to grow. In Ukraine, the franchise market is developing rapidly, especially in the service sector. The rate of use of the franchise in the restaurant business is high. The hotel business is developing at a much slower pace. Even animation programs, which were the competitive advantages of individual hotels, have undergone significant changes, namely they have been banned and there are still significant quarantine restrictions on animation programs. Therefore, current trends that affect the development of hotel and restaurant business are: the creation of a delivery system or focus on the production of takeaway dishes; growing demand for casual restaurants that can cook good food, but the cost will be lower than in expensive restaurants; distribution of self-service kiosks; use of QR-codes – menu instead of traditional menu; creation of animation programs with quarantine restrictions; development of virtual and augmented reality, which allows you to create virtual tours that can demonstrate the capabilities of the institution before booking; use of robots in restaurants (especially in the kitchen) and hotels. Therefore, it is advisable to study the practice of franchising in the regional aspect.
Keywords: franchise; hotel; restaurant; quarantine; development